Hadapi pandemi covid-19 dengan perilaku hidup bersih dan sehat (PHBS) di era new normal - Recta Olivia Umboro; Fitri Apriliany; Vera Fitriya Ersalena (University of Islam Malang, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new type of coronavirus that can be transmitted to humans. The government of West Nusa Tenggara Province confirmed 3.082 positive cases of Covid-19 with 223 cases in Central Lombok by September 2020. Geographically, Penujak is one of villages in Central Lombok close to Lombok International Airport which is an entry point for local and international tourists. Thus, Lecturers of Division of Pharmacy, Bumigora University conducted Community Service Activity entitled “Sosialisasi Hidup Sehat dan Bersih di Tengah Pandemi Covid-19 dan Pelatihan Pembuatan Hand Sanitizer” which aims to educate societies how to start healthy life. The community service was done by socializing for healthy living and adapting to the new normal, and training to formulating hand sanitizer properly. Therefore, new insights and better understanding were gained in order to live healthily and to implement their skills to produce proper standar for hand sanitizer.